ORC Performance Study with R32 and R134a Using Biomass as an Energy Source - Lalu Muh Fathul Aziz Al Azhari; Muhamad Yulianto; Edy Hartulistiyoso (The University of Lampung, 2025)
The use of fossil energy as the main source of primary energy reached 84.7%, with electricity consumption in Indonesia of 1,173 kWh/capita, dominated by fossil fuels (67.21%). The decline in fossil energy reserves requires the development of alternative technologies such as the Organic Rankine Cycle (ORC) that can operate at low to medium temperatures (60°C-200°C). This research was carried out in 2 ways, experiment, and simulation. Experiments were carried out to determine the temperature that can be generated in the evaporator of ORC from the flue gas flow from burning biomass. Simulations were carried out to evaluate the performance of the ORC cycle with working fluids R32 and R134a and the contribution of CO2 to the environment using the LCCP (Life Cycle Climate Performance) method. The analysis involves measuring the outlet temperature of the evaporator. The research results show that the validation for predicting the output temperature of the ORC evaporator is very good with a Mean Absolute Percentage Error (MAPE) value of <10%. Simulation results show that in this study, R32 performed better than R134a, with a net power of 0.13 kW at a temperature of 86.83℃. LCCP analysis results show that R32 has lower direct emissions than R134a, with better LCCP values. Keywords: LCCP, Organic rankine cycle, R134a, R32, Simulation, Work output.